2021
DOI: 10.14202/vetworld.2021.3164-3169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of L-carnitine supplementation on the in vitro developmental competence and cryotolerance of buffalo embryos

Abstract: Background and Aim: Despite many trials, buffalo embryos have poor cryosurvivability because of their high lipid content. L-carnitine was found to be a lipid-reducing agent when added to oocyte and embryo culture media. The study aimed to determine the most effective concentration of L-carnitine to improve the oocyte developmental competence and cryotolerance of buffalo embryos. Materials and Methods: In vitro maturation and embryo culture media were supplemented with four concentrations of L-carnitine: 0 (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
1
0
3
Order By: Relevance
“…of fertilization in both young and aged mice and decreased the mean of embryonic development of the 2-cell embryo of grade D, that characterized by unequal size blastomeres and sever fragmentation. It has been demonstrated that LC increases the preimplantation and developmental competence of embryos in experimental animals, due to the improvement of cytoplasmic and nuclear maturation of oocytes that play an initial role in the consequent development of fertilized oocyte to embryo, and the reduction of ROS levels 27 , which may be due to its vital role in increasing glutathione (GSH) levels inside the cells that can prevent free radical damage to embryos 28 . On the other hand, it has been reported that LC tends to induce nuclear maturity and increase the number of early embryos in camels 29 .…”
Section: L-carnitine Improves Preimplantation Embryos Developmentmentioning
confidence: 99%
“…of fertilization in both young and aged mice and decreased the mean of embryonic development of the 2-cell embryo of grade D, that characterized by unequal size blastomeres and sever fragmentation. It has been demonstrated that LC increases the preimplantation and developmental competence of embryos in experimental animals, due to the improvement of cytoplasmic and nuclear maturation of oocytes that play an initial role in the consequent development of fertilized oocyte to embryo, and the reduction of ROS levels 27 , which may be due to its vital role in increasing glutathione (GSH) levels inside the cells that can prevent free radical damage to embryos 28 . On the other hand, it has been reported that LC tends to induce nuclear maturity and increase the number of early embryos in camels 29 .…”
Section: L-carnitine Improves Preimplantation Embryos Developmentmentioning
confidence: 99%
“…Khanmohammadi et al (2016), informaron el incremento del porcentaje de blastocistos (P < 0.01) y el número total de células de embriones de ratón debido al efecto antioxidante de la L-carnitina a una concentración de 0.5 mg/mL. Otros autores, refieren que la L-carnitina durante la MIV, reduce la toxicidad del embrión inducida por el estrés oxidativo al disminuir las ERO y aumentar el GSH intracelular en ovocitos ovinos (Mishra et al, 2016) y aumenta la tasa de división y el porcentaje de embriones de búfalo (El-Sokary et al, 2021).…”
Section: Parámetro Grupo 1 Grupo 2 Controlunclassified
“…De la misma manera, la adición de L-carnitina a una concentración de 0.5 mM al medio de MIV, mejora el desarrollo del ovocito, la competencia y criotolerancia de embriones de búfalo posterior a la desvitrificación, pero no después de 24 h de cultivo. (El-Sokary et al, 2021).…”
Section: Parámetro Grupo 1 Grupo 2 Controlunclassified
See 1 more Smart Citation